Changes in intrahousehold labor allocation to environmental goods collection: a case study from rural Nepal, 1982 to 1997 - Cooke, Priscilla A. (International Food Policy Research Institute, 2000)
This study explores the impact of changes in environmental conditions on intrahousehold labor allocation to the collection of environmental goods such as fuelwood and leaf fodder for a sample of rural Nepali households. Using household-level panel data collected in 1982 and 1997, the study finds that household collection time significantly increases with measures of environmental resource scarcity, and that the increase appears to come almost equally from men and women. Additionally, the results of this study indicate that household collection burdens are significantly lower in 1997 than in 1982, and that women have seen the largest decrease in their time spent collecting. The picture is not an entirely rosy one, however, as consumption of environmental goods is also significantly lower in 1997 compared to 1982. The results taken together indicate that one should not hastily attribute decreases in collection labor burdens to successful forest rehabilitation in areas managed by forest user groups. In this case it appears that lower collection times are principally due to reduced consumption and increased collection from private land.